Google Slides as a Creative Solution to Improve Arabic Vocabulary Mastery: Google Slides sebagai Solusi Kreatif untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Isima, Nuranisa; Annisa Raina Khairani; Eka Meitya P. Akase (Language Development Center, 2025)
Background: This research is based on the importance of vocabulary mastery as an indicator of language learning success. Learning Arabic at Alhijrah Kindergarten, which uses flashcards too often, causes student boredom. With interactive features like videos, animations, and links, Google Slides offers a more engaging and fun alternative to vocabulary learning. Purpose: This study aims to test the effectiveness of using Google Slides in improving students’ mastery of Arabic vocabulary in Alhijrah Islamic Kindergarten. Method: This research design is a quantitative experiment that tests the effectiveness of Google Slides on the mastery of Arabic vocabulary of Alhijrah Islamic Kindergarten students. Result and Discussion: The results showed a significant increase in students’ vocabulary mastery after using Google Slides, with an average posttest score of 80.75 compared to the average pretest score of 47.75. In the experimental class, the average value difference between the pretest and the posttest was -28,250, with a standard deviation of 11,271. As for the control class, the average score difference between the pretest and the posttest was -10,000, with a standard deviation of 6,283. The output results of the paired sample test showed that the significance value (p-value) was 0.000. Because the value obtained from 0.000 was less than 0.05, it can be concluded that Google Slides effectively improves students’ vocabulary mastery. Conclusion and Implications: Google Slides has proven effective in improving the mastery of Arabic vocabulary in Alhijrah Islamic Kindergarten. Students significantly improve their remembering and understanding of new vocabulary through its interactive and multimedia features, contributing to their Arabic language skills. As a research implication, Alhijrah Islamic Kindergarten teachers should regularly integrate Google Slides in learning Arabic vocabulary to create more interactive learning.